Impact of lower uterine segment involvement in type II endometrial cancer and the unique mutational profile of serous tumors - Liron Kogan; David Octeau; Zainab Amajoud; Jeremie Abitbol; Ido Laskov; Alex Ferenczy; Manuela Pelmus; Neta Eisenberg; Roy Kessous; Susie Lau; Amber Yasmeen; Walter H. Gotlieb; et al. (Elsevier, 2018)
Objective: Evaluation of the impact of lower uterine segment involvement (LUSI) in type II endometrial cancer, and mutational profile of uterine papillary serous carcinomas (UPSC). Methods: Retrospective cohort study comparing patients with type II endometrial cancer with LUSI to patients without LUSI. Genes commonly implicated in carcinogenesis were analyzed in a subgroup of 42 patients with UPSC using next generation sequencing. Results: 83 patients with type II endometrial cancer were included in the study, of these, LUSI was diagnosed in 31.3%. During a median follow-up of 45.5 months, patients with LUSI developed more local and distant recurrences (local: 19.2% vs. 3.5%, P = .03; distant: 50% vs. 17.5%, P = .004) and progression events (73.1% vs. 26.3%, P < .001), with shorter mean progression-free survival (16 months compared to 26.5 months, P < .01). In a multivariate analysis, LUSI was the only significant pathological factor, associated with a 2.9-fold increase in the risk of progression (P = .007), and a 2.6-fold increase in the risk of death (P = .02). In the subgroup of patients with UPSC, mutations were identified in 54 genes, including TP53 (80%), PPP2R1A (40%), and PTEN (22.5%). Frequent mutations in the PTEN-PI3K-AKT signaling pathway were found in patients with tumor in the upper uterine segment only (P = .04), with PTEN being mutated in 29% of the samples (P = .07). Conclusion: Type II endometrial cancers presenting in the LUS have a significantly worse prognosis and this might be associated with a unique mutational profile. Keywords: Lower uterine segment, Uterine papillary serous carcinoma, Type II endometrial cancer, Sequencing, Gene analysis, PTEN mutation